Pengaruh Strategi Pengajaran dan Sikap Siswa terhadap Hasil Belajar Pembelajaran Konsep IPS di Sekolah Dasar - Punaji Setyosari (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
The aims of the study were to examine the effects of various learning strategies, that is, using examples, non-examples, or text-books, on the outcomes of learning social science. Pretest and post test were assigned to the subjects, 129 fifth graders, who had been devided, in three groups. Multiple comparisons of the three groups indicate that the subjects taught using examples and non-examples out performed those taught using textbooks.